The “obesity paradox” in patients with atrial fibrillation: Insights from the Gulf SAFE registry - Li, Yan-Guang; Xie, Peng-Xin; Alsheikh-Ali, Alawi A.; AlMahmeed, Wael; Sulaiman, Kadhim; Asaad, Nidal; Liu, Shu-Wang; Zubaid, Mohammad; Lip, Gregory Y. H. (Frontiers in Cardiovascular Medicine, 2022)
Background: The prognostic impact of obesity on patients with atrial fibrillation (AF) remains under-evaluated and controversial. Method: Patients with AF from the Gulf Survey of Atrial Fibrillation Events (Gulf SAFE) registry were included, who were recruited from six countries in the Middle East Gulf region and followed for 12 months. A multivariable model was established to investigate the association of obesity with clinical outcomes, including stroke or systemic embolism (SE), bleeding, admission for heart failure (HF) or AF, all-cause mortality, and a composite outcome. Restricted cubic splines were depicted to illustrate the relationship between body mass index (BMI) and outcomes. Sensitivity analysis was also conducted. Result: A total of 1804 patients with AF and recorded BMI entered the final analysis (mean age 56.2±16.1 years, 47.0% female); 559 (31.0%) were obese (BMI over 30kg/m2). In multivariable analysis, obesity was associated with reduced risks of stroke/systematic embolism (adjusted odds ratio [aOR] 0.40, 95% confidence interval [CI] 0.18-0.89), bleeding (aOR 0.44, 95%CI 0.26-0.74), HF admission (aOR 0.61, 95%CI 0.41-0.90) and the composite outcome (aOR 0.65, 95%CI 0.50-0.84). As a continuous variable, higher BMI was associated with lower risks for stroke/SE, bleeding, HF admission, all-cause mortality, and the composite outcome as demonstrated by the accumulated incidence of events and restricted cubic splines. This “protective effect” of obesity was more prominent in some subgroups of patients. Conclusion: Among patients with AF, obesity and higher BMI were associated with a more favorable prognosis in the Gulf SAFE registry. The underlying mechanisms for this ‘obesity paradox’ merit further exploration.